Analisis Pengaruh Likuiditas dan Opini Audit terhadap Ketepatan Waktu dalam Pelaporan Keuangan pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Novien Rialdy (Formosa Journal of Computer and Information Science, 2022)
High level of liquidity in the company indicates that the company is able to meet its short term obligations properly. The audit opinion is given to know the level of the company's survival. Liquidity describes the company's ability to pay short-term obligations. Sheet audit opinion is the responsibility of public accountants to give an opinion on the fairness of financial statements prepared by management. Timeliness means that the information must be available when needed. The research method is quantitative, the kind of research is quantitative descriptive, while the nature of this research is explanatory research. This study population were manufacturing companies listed in Indonesia Stock Exchange in 2019-2021 period, amounting to 145 companies. This research sample consisted of 375 samples taken from samples of 125 companies.The study found that liquidity and audit opinion do not affect the timeliness of financial reporting on manufacturing companies listed in Indonesia Stock Exchange in 2019-2021 period with significant value is much greater than the significance level (0.05).